Leydig cell tumor of testis- a rare case report - Arora, Sheetal; Pujani, Mukta; Rana, Deepshikha; Chaudhaury, Narendra (International Surgery Journal, 2017)
Leydig cell tumors(LCTs) of testis are rare testicular tumors of male gonadal interstitium. Although rare, they are most common sex cord stromal tumors and comprise 1-3 % of all testicular neoplasms. They usually occur in fourth to sixth decade. In young patients, they are mostly benign and in adults it can be malignant in about 10 % cases. The incidence of Leydig cell tumors is gradually increasing every year which might be attributed to increased use of radiological techniques and subsequent early detection of tumors that have not been found in historical series. Here we report a case of benign Leydig cell tumor testis in a 45-year-old male who presented with left sided testicular mass. The patient subsequently underwent high inguinal orchidectomy. Histopathological examination showed benign pure Leydig cell tumor. Serological investigations revealed normal testosterone levels, DHEA and androstenedione levels. Immunohistochemical staining for inhibin showed fine granular cytoplasmic positivity and diffuse positive staining for Melan-A which further confirmed the diagnosis. The endocrine profile and imaging investigations of such patients might be normal and patients can be totally asymptomatic. However periodic follow up of endocrine profile and imaging must be done as many cases have been reported which had deranged endocrine levels and appearance of atypical symptoms even after years of unilateral orchidectomy. Our case also presents with normal hormonal levels, henceforth for a better prognosis we must identify benign LCTs and do long term follow up.